Effectiveness of Online PAI Learning During the Covid 19 Pandemic at MAUWH Tambakberas Jombang - M Wafiyul Ahdi; Muhammad Ubaidillah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Education has an important role in building the Nation of Indonesia, one of which is in the learning process. Learning is said to be successful if the learning process runs effectively in accordance with the learning plan and objectives. In Indonesia, especially in MAUWH Tambakberas Jombang there was a change in the learning process that was initially face-to-face in school to Be Online ( Remote) because of the Covid 19 pandemic, therefore, this study aims to: 1.) Knowing the learning process pai online at MAUWH. 2.) Know the effectiveness of pai learning online at MAUWH. 3.) Know the advantages and disadvantages during the pai learning process online at MAUWH. In this case the researchers took the title